Aromatic 1, 2‐Azaborinin‐1‐yls as Electron‐Withdrawing Anionic Nitrogen Ligands for Main Group Elements. Issue 11 (10th January 2023) - Lindl, Felix; Lamprecht, Anna; Arrowsmith, Merle; Khitro, Eugen; Rempel, Anna; Dietz, Maximilian; Wellnitz, Tim; Bélanger‐Chabot, Guillaume; Stoy, Andreas; Paprocki, Valerie; Prieschl, Dominik; Lenczyk, Carsten; et al.
Abstract: The 2‐aryl‐3, 4, 5, 6‐tetraphenyl‐1, 2‐azaborinines 1‐EMe3 and 2‐EMe3 (E=Si, Sn; aryl=Ph (1 ), Mes (=2, 4, 6‐trimethylphenyl, 2 )) were synthesized by ring‐expansion of borole precursors with N3 EMe3 ‐derived nitrenes. Desilylative hydrolysis of 1‐ and 2‐SiMe3 yielded the corresponding N‐protonated azaborinines, which were deprotonated with n BuLi or MN(SiMe3 )2 (M=Na, K) to the corresponding group 1 salts, 1‐M and 2‐M . While the lithium salts crystallized as monomeric Lewis base adducts, the potassium salts formed coordination polymers or oligomers via intramolecular K⋅⋅⋅aryl π interactions. The reaction of 1‐M or 2‐M with CO2 yielded N‐carboxylate salts, which were derivatized by salt metathesis to methyl and silyl esters. Salt metathesis of 1‐M or 2‐M with methyl triflate, [Cp*BeCl] (Cp*=C5 Me5 ), BBr2 Ar (Ar=Ph, Mes, 2‐thienyl), ECl3 (E=B, Al, Ga) and PX3 (X=Cl, Br) afforded the respective group 2, 13 and 15 1, 2‐azaborinin‐2‐yl complexes. Salt metathesis of 1‐K with BBr3 resulted not only in N‐borylation but also Ph‐Br exchange between the endocyclic and exocyclic boron atoms. Solution 11 B NMR data suggest that the 1, 2‐azaborinin‐2‐yl ligand is similarly electron‐withdrawing to a bromide. In the solid state the endocyclic bond length alternation and the twisting of the C4 BN ring increase with the sterics of the substituents at the boron and nitrogen atoms, respectively. Regression analyses revealed that the downfield shift of the endocyclic 11 B NMR resonances is linearly correlated to both the degree of twisting of the C4 BN ring and the tilt angle of the N‐substituent. Calculations indicate that the 1, 2‐azaborinin‐1‐yl ligand has no sizeable π‐donor ability and that the aromaticity of the ring can be subtly tuned by the electronics of the N‐substituent. Abstract : N‐protonated, N‐lithiated and N‐stannylated 1, 2‐azaborinines provide versatile platforms for the synthesis of new group 1–2 and 13–15 derivatives of the 1, 2‐azaborinin‐1‐yl ligand. NMR‐spectroscopic, X‐ray crystallographic and computational analyses show that the aromatic 1, 2‐azaborinin‐1‐yl ligand is a purely electron‐withdrawing N‐ligand lacking π‐donor ability.